2018
DOI: 10.1080/2162402x.2018.1553477
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating natural killer cell cytotoxicity against solid tumors using a microfluidic model

Abstract: 2019) Evaluating natural killer cell cytotoxicity against solid tumors using a microfluidic model, OncoImmunology, 8:3, 1553477, ABSTRACT Immunotherapies against solid tumors face additional challenges compared with hematological cancers. In solid tumors, immune cells and antibodies need to extravasate from vasculature, find the tumor, and migrate through a dense mass of cells. These multiple steps pose significant obstacles for solid tumor immunotherapy and their study has remained difficult using classic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 47 publications
(53 reference statements)
0
99
0
1
Order By: Relevance
“…In this work, we developed a tumor‐lymphatic microfluidic device for coculturing tubular lymphatic vessels and breast cancer cells to study their crosstalk. The design of the device was based on previous methods for making endothelial vessels in natural extracellular matrix (ECM) hydrogel and for coculturing these vessels with breast cancer cells . The device comprised a chamber to inject an unpolymerized collagen type I hydrogel and two adjacent PDMS rods suspended in the chamber ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we developed a tumor‐lymphatic microfluidic device for coculturing tubular lymphatic vessels and breast cancer cells to study their crosstalk. The design of the device was based on previous methods for making endothelial vessels in natural extracellular matrix (ECM) hydrogel and for coculturing these vessels with breast cancer cells . The device comprised a chamber to inject an unpolymerized collagen type I hydrogel and two adjacent PDMS rods suspended in the chamber ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, our results demonstrate that different breast cancer subtypes alter lymphatic vessel physiology to different degrees and that our model can be used to better understand the tumor‐lymphatic crosstalk that contributes to lymphatic vessel dysfunction. Previous studies have analyzed the chemokines secreted by breast cancer cells, including MCF7 and MDA‐MB‐231 cells . These studies have identified multiple chemokines that could be driving the lymphangiogenic process observed in the microfluidic device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 163 ] Copyright 2018, Taylor & Francis. C) 3D microfluidic device for MDOTS/PDOTS culture.…”
Section: Other Relevant Immunocompetent Ooc Modelsmentioning
confidence: 99%
“…Moreover, a 3D breast cancer model was developed to study NK cell immunotherapies and antibody‐dependent cell cytotoxicity (ADCC), in which breast cancer cell (MCF‐7) spheroids were encapsulated in a collagen hydrogel, individually or in combination with NK‐92 or the CD16‐positive NK‐92, whereas two lateral lumens were seeded with HUVECs (Figure 5B a). [ 163 ] The antiepithelial cell adhesion molecule (EpCAM) antibody was introduced through the endothelialized channel or directly incorporated in the hydrogel to understand the dynamics of antibodies supplied and their effect on NK cytotoxicity. The results indicated that antibodies present in the TME were taken up by the tumor cells, whereas the penetration capacity of the antibodies into the spheroids was hindered by endothelial tight junctions.…”
Section: Other Relevant Immunocompetent Ooc Modelsmentioning
confidence: 99%